2010
DOI: 10.1007/s10457-010-9288-9
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry and grass buffer effects on water quality in grazed pastures

Abstract: Conservation practices including agroforestry and grass buffers are believed to reduce nonpoint source pollution (NPSP) from pastured watersheds. Agroforestry, a land management practice that intersperses agricultural crops with trees, has recently received increased attention in the temperate zone due to its environmental and economic benefits. However, studies are limited that have examined buffer effects on the quality of water from grazed pastures. Six treatment areas, two with agroforestry buffers, two wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 20 publications
2
20
0
1
Order By: Relevance
“…On a "paired" watershed study in Missouri, agroforestry and grass buffer strips reduced phosphorus and nitrogen loss from a corn-soybean rotation [88]. The perennial vegetation increases above-ground biomass that slows runoff and can trap as much as 95% of the sediment at risk of being lost [91], while the below-ground roots can take up 80% or more of excess nutrients as well as hosting microbial populations that can break down pesticides [68,90,92].…”
Section: Benefits Of Agroforestrymentioning
confidence: 99%
“…On a "paired" watershed study in Missouri, agroforestry and grass buffer strips reduced phosphorus and nitrogen loss from a corn-soybean rotation [88]. The perennial vegetation increases above-ground biomass that slows runoff and can trap as much as 95% of the sediment at risk of being lost [91], while the below-ground roots can take up 80% or more of excess nutrients as well as hosting microbial populations that can break down pesticides [68,90,92].…”
Section: Benefits Of Agroforestrymentioning
confidence: 99%
“…Agroforestry combined with grass can be used as buffers to improve water quality in a watershed. Udawatta et al (2010) tested two agroforestry buffers, two grass buffers, and two controls (no buffers) on water quality of grazed pastures. They observed that on pasture watersheds, the agroforestry and grass buffers reduced runoff and reduced non-point source pollution compared with the control.…”
Section: Soil Erosion Control and Riparian Buffersmentioning
confidence: 99%
“…With conventional agricultural systems, typically less than 50 % of applied N and P is utilized by crops. In consequence, excess fertilizer moves beyond the reach of plants through runoff or leaching to deeper soil layers, contaminating groundwater reserves and decreasing water quality (Udawatta, Garrett, & Kallenbach, 2010). Therefore, agroforestry management practices can be used as a strategy to provide clean water (Shibu, 2009).…”
Section: Uribe Y Petit (2007) Analizaron La Influencia De La Cubiertamentioning
confidence: 99%